2016
DOI: 10.1007/s13644-015-0236-z
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Prayer in Transforming Individuals and Marital Relationships: A Qualitative Examination of Christian, Jewish, and Muslim Families

Abstract: Prayer is a widely practiced religious behavior. Research has associated prayer with various physical, psychological, and relational benefits. This study used in-depth, interview-based qualitative methods to explore how prayer may foster improvement in married individuals as well as in couples’ relationships in a richly diverse sample of 184 religious couples (N = 368 individuals). Qualitative data analyses revealed the following related themes: (a) prayer is a catalyst for change; (b) prayer facilitates humil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Historically families and religions have been intertwined and have been a means of passing on values from one generation to the next (Bengtson et al, 2013). Several studies have found that parents are the primary source of religious influence on children (Bao, Whitbeck, Hoyt, & Conger, 1999; Denton, 2012; McMurdie, Dollahite, & Hardy, 2013; Myers, 1996), particularly through practices like prayer in families (Chelladurai, Dollahite, & Marks, 2018; Hatch et al, 2016). In a 12-year longitudinal study of parents and their adult offspring, Myers (1996) concluded that parental religiosity is the most significant factor in the religious involvement of adult children.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Historically families and religions have been intertwined and have been a means of passing on values from one generation to the next (Bengtson et al, 2013). Several studies have found that parents are the primary source of religious influence on children (Bao, Whitbeck, Hoyt, & Conger, 1999; Denton, 2012; McMurdie, Dollahite, & Hardy, 2013; Myers, 1996), particularly through practices like prayer in families (Chelladurai, Dollahite, & Marks, 2018; Hatch et al, 2016). In a 12-year longitudinal study of parents and their adult offspring, Myers (1996) concluded that parental religiosity is the most significant factor in the religious involvement of adult children.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In conflictual situations, individual and couple prayer reportedly deescalated hostile emotions, facilitated empathy, and encouraged couple responsibility for reconciliation and problem solving (Butler et al, 1998). Similarly, prayer appeared to facilitate humility and positivity in individuals and improving communication and understanding among couples (Hatch et al, 2016(Hatch et al, , 2017. Inward prayers, including confession, enabled individuals to introspect, become less defensive, and have empathy toward family members and also seemed to have a bonding effect by facilitating family togetherness (Marsh & Dallos, 2001).…”
Section: How Does Prayer Achieve Relational Outcomes?mentioning
confidence: 99%
“…Although prayer in relationships has been shown to have mostly positive transformational effects (Goodman, Dollahite, Marks, & Layton, 2013;Hatch et al, 2016Hatch et al, , 2017, like other aspects of religion, it also has the potential to be damaging, when misunderstood or misapplied (Dollahite, Marks, & Dalton, 2018). As a corollary to findings that suggest different types of prayers have different individual subjective well-being outcomes (Ai, Tice, Huang, Rodgers, & Bolling, 2008), certain approaches to prayer in relationships can also have negative outcomes.…”
Section: Can Certain Approaches To Prayer Harm Familymentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, an influx of studies has drawn attention to the role of prayer in couple relationship quality (Beach et al 2011(Beach et al , 2008a(Beach et al , 2008bFincham and Beach 2014;Fincham et al 2008;Fincham and May 2017;Hatch et al 2016;Marks 2008;Sullivan and Karney 2008;Worthington 2008). Much of the research on prayer and couple relationship quality has centered on how prayer strengthens relational bonds (Beach et al 2011;Ellison et al 2010;Goodman et al 2013;Olson et al 2015) and how these bonds are specifically strengthened through partner petitionary prayer and intercession (Fincham and Beach 2014;Fincham et al 2008;Hall et al 2008;Lambert et al 2010;Mahoney and Cano 2014;Pollard et al 2014).…”
Section: Introductionmentioning
confidence: 99%